Coral reef adventure [videorecording (DVD)] - MacGillivray, Greg; Neeson, Liam; Hall, Howard, 1949- (Image Entertainment, 2003)
"Ocean explorers Howard and Michele Hall turn their love for the ocean and their concern for the future of the world's coral reefs into action. With Jean-Michel Cousteau, deep reef scientist Richard Pyle and Fijian diver Rusi Vulakoro, the Halls explore and capture on film the dazzling underwater world of coral reefs, magical places here on Earth."--Container.